Evaluating wafer inspection and cleaning with standard particles - Liu B.Y.H.; Yoo S.-H.; Chae S.-K.; Sun J.J.; Christenson K.; Butterbaugh J.; Weygand J.F.; Narayanswami N. (My University, 2025)
To study the response of a wafer surface scanner and perform cleaning system evaluation, a process particle deposition system was used to deposit polystyrene latex (PSL) spheres and real-world process particles of Si, SiO2, W and Cu on wafers. It was found that the scanner response is affected by the particle refractive index. The measured cleaning efficiency was found to be dependent on particle material.